Italy’s state budget - G.E.M., G.E.M. (PSL Quarterly Review, 2014)
The article analyses the development of the Italian financial situation in the first three years of this post-war period. After some introductory remarks illustrating the structure of the Italian budget, the author compares the original estimates presented at the opening of each financial year with the final results, so as to stress more especially the difficulties arising from the environmental conditions that have had to be faced in the work of financial rehabilitation. The author then describes the movement of assessed receipts and pledged expenditure, dwelling particularly on the growth of the yield of taxation and on some new items that now appear in the budget, before studying some of the problems arising from the connections between the current budget and the cash account. He then examines the latter from the point of view both of the “budget transactions” and of the Treasury operations, and illustrates the distribution of the charges incurred for covering current payments, classifying all the data on total receipts so as to show the nature of the sources from which they are obtained. The article closes with an examination of the growth of the national debt and of the several items of which it is composed. JEL: H61